The Mobius Strip: Team Teachers Reflecting on Disability Studies and Critical Thinking - Cypher, Joy; Martin, Deb (Disability Studies Quarterly, 2008)
This essay combines personal and academic reflection on teaching critical thinking through a disability studies perspective, and is illustrated by our experiences and insights teaching an undergraduate, general education course. We began with the understanding that disability studies is itself a critical engagement with a dominant ideology of bodily normalcy, value, access and power. We perhaps assumed that to teach disability studies at all would already entail critical thinking. But our experiences teaching this class challenged our beginning assumptions and raised the following questions, which form the focus for this discussion: Do disability studies classes (or any classes for that matter) enact critical thinking agendas by their content alone? What is the role of DS pedagogy in the goal of teaching critical thinking, and how can the teaching itself work to facilitate this goal by all engaged parties? We suggest that teachers incorporating DS consider the concept of "critical progress" rather than assuming that critical thinking is an end goal.